PENGEMBANGAN APLIKASI PENGOLAHAN DATA CUACA PADA STASIUN METEOROLOGI MARITIM PONTIANAK - Asynuzar, Novianto (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
The data encoding of meteorologyobservation that is still done manually by the observeroften create the wrong result of the code. On the otherhand, the unstructurized database makes thepresentation of data quickly and accurately beconstrained. Therefore the aplication that able tomanage the data of observation structurally and showit into information that is easy to understand isneeded.Test results have shown that the application is capableto encode the weather data automatically andgenerate output like monthly reports and other reportsas required of Stasiun Meteorologi MaritimPontianak. It can be concluded that the system hadbeen running according to the purpose of fieldwork.